Modern construction management - Harris, Frank; McCaffer, Ronald; Edum-Fotwe, Francis (New Delhi Wiley India, 2013)
This new edition of a core undergraduate textbook for construction managers reflects current best practice, topical industry preoccupations and latest developments in courses and fundamental subjects for students. While the construction process still requires traditional skills, changes over recent decades today demand improved understanding of modern business, production and contractual practices. The authors have responded accordingly and the book has undergone a thorough re-write, eliminating some of the older material and adding new processes now considered essential to achieving lean construction.
Keywords: Civil Engineering